Robust Virome Profiling and Whole Genome Reconstruction of Viruses and Viroids Enabled by Use of Available mRNA and sRNA-Seq Datasets in Grapevine (Vitis vinifera L.) - Sidharthan, V. Kavi; Sevanthi, Amitha Mithra; Jaiswal, Sarika; Baranwal, V. K. (Frontiers in Microbiology, 2020)
Next-generation sequencing (NGS) based virome analyses of mRNA and sRNA have recently become a routine approach for reliable detection of plant viruses and viroids. In the present study we identified the viral/viroidal spectrum of several Indian grapevine cultivars and reconstructed their whole genomes using the publically available mRNAome and sRNAome datasets. Twenty three viruses and viroids (including two variants of grapevine leafroll associated virus 4) were identified from two tissues (fruit peels and young leaves) of three cultivars among which nine unique grapevine viruses and viroids were identified for the first time in India. Irrespective of the assemblers and tissues used, the mRNA based approach identified more acellular pathogens than the sRNA based approach across cultivars. Further, the mRNAome was on par with the whole transcriptome in viral identification. Through de novo assembly of transcriptomes followed by mapping against reference genome, we reconstructed 19 complete/near complete genomes of identified viruses and viroids. The reconstructed viral genomes included four larger RNA genomes (>13 kb), a DNA genome (RG grapevine geminivirus A), a divergent genome (RG grapevine virus B) and a genome for which no reference is available (RG grapevine virus L). A large number of SNPs detected in this study ascertained the quasispecies nature of viruses. Detection of three recombination events and phylogenetic analyses using reconstructed genomes suggested the possible introduction of viruses and viroids into India from several continents through the planting material. The whole genome sequences generated in this study can serve as a resource for reliable indexing of grapevine viruses and viroids in quarantine stations and certification programs.